Researching education : : data, methods and theory in educational enquiry / David Scott and Robin Usher. - Scott, David, 1951- (Institute of Education series, 2000)
David Scott and Robin Usher study the theory and practice of researching education. Unlike other books on research, it seeks to explore and explain educational processes, systems and institutions.